Acute and chronic role of nitric oxide, renin-angiotensin system and sympathetic nervous system in the modulation of calcium sensitization in Wistar rats - Brunová, Aneta; Bencze, Michal; Behuliak, Michal; Zicha, Josef (Physiological research, 2015)
Principal vasoactive systems - renin-angiotensin system (RAS), sympathetic nervous system (SNS), nitric oxide (NO) and prostanoids - exert their vascular effects through the changes in calcium levels and/or calcium sensitization. To estimate a possible modulation of calcium sensitization by the above vasoactive systems, we studied the influence of acute and chronic blockade of particular vasoactive systems on blood pressure (BP) changes elicited in conscious normotensive rats by acute dose-dependent administration of Rho-kinase inhibitor fasudil. Adult male chronically cannulated Wistar rats were used throughout this study. The acute inhibition of NO synthase (NOS) by L-NAME enhanced BP response to fasudil, the effect being considerably augmented in rats deprived of endogenous SNS. The acute inhibition of prostanoid synthesis by indomethacin modified BP response to fasudil less than the acute NOS inhibition. The chronic NOS inhibition caused moderate BP elevation and a more pronounced augmentation of fasudil-induced BP changes compared to the effect of acute NOS inhibition. This indicates both short-term and long-term NO-dependent attenuation of calcium sensitization. Long-term inhibition of RAS by captopril caused a significant attenuation of BP changes elicited by fasudil. In contrast, a long-term attenuation of SNS by chronic guanethidine treatment (in youth or adulthood) had no effect on BP response to fasudil, suggesting the absence of SNS does not affect calcium sensitization in vascular smooth muscle of normotensive rats. In conclusion, renin-angiotensin system contributes to the long-term increase of calcium sensitization and its effect is counterbalanced by nitric oxide which decreases calcium sensitization in Wistar rats.
Keywords: Calcium; Male; sympatický nervový systém; Rats, Wistar; kyselina dusičná; cévní rezistence; vápník; Adaptation, Physiological; mužské pohlaví; potkani Wistar; fyziologická adaptace; Vasoconstriction; krysa rodu Rattus; Animals; krevní tlak; Sympathetic Nervous System; renin-angiotensin systém; Vascular Resistance; zvířata; Renin-Angiotensin System; Rats; Nitric Acid; Blood Pressure; vazokonstrikce